Transparent Boundary Conditions for Elastic Anisotropic VTI Media: Axially Symmetric Case (Communications in Computational Physics, 2020)
Transparent boundary conditions (TBCs) for anisotropic vertical transverseisotropic VTI medium are formulated for the axially symmetric case. The high accuracy of the derived TBCs and their long-time stability are demonstrated in numericalexperiments. The TBCs are represented in terms of the vertical component of the velocity vector and tangential component of the stress tensor that facilitates the easy implementation of the boundary condition into the finite-difference staggered-grid scheme.